2016
DOI: 10.1155/2016/7836784
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Datar-Mathews Method and the Fuzzy Pay-Off Method through Numerical Results

Abstract: The paper compares numerically the results from two real option valuation methods, the Datar-Mathews method and the fuzzy pay-off method. Datar-Mathews method is based on using Monte Carlo simulation within a probabilistic valuation framework, while the fuzzy pay-off method relies on modeling the real option valuation by using fuzzy numbers in a possibilistic space. The results show that real option valuation results from the two methods seem to be consistent with each other. The fuzzy pay-off method is more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The triangle’s corner points are defined by the base-, worst-, and best-case scenarios of the investment, while the height is always 1. Kozlova et al ( 2016 ) show that the results of the method are comparable to the results of similar real option approaches such as Mathews et al ( 2007 ). The method can be visualized, which makes it user friendly and intuitive, as it will be shown in the following sections.…”
Section: Literature Reviewmentioning
confidence: 67%
“…The triangle’s corner points are defined by the base-, worst-, and best-case scenarios of the investment, while the height is always 1. Kozlova et al ( 2016 ) show that the results of the method are comparable to the results of similar real option approaches such as Mathews et al ( 2007 ). The method can be visualized, which makes it user friendly and intuitive, as it will be shown in the following sections.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Furthermore, they used fuzzy volatility and dividend variables. Kozlova, Collan and Luukka (2016) compared the Datar-Mathews method based on Monte Carlo simulation, which is probability-based, and the fuzzypayoff method, which is possibility-based, and observed that the results are compliant with each other. Aranda, Arango and Lianos (2016) evaluated the distribution center of an Auxiliary Rail Freight Terminal project by using fuzzy logic and American call options and also in comparison with the Black-Scholes model.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The results from the method are intuitively understandable and easily be visualized. Uncertainty is presented in a way that is similar to the one commonly used in presenting the results of, e.g., Monte Carlo simulation (Kozlova et al, 2016).…”
Section: Results and Visualizationmentioning
confidence: 99%
“…The FPOM has also previously been used in the analysis of renewable energy investments (Kozlova et al, 2016) and other applications of the method include, e.g., energy and oil investments (Bednyagin and Gnansounou, 2011;Borges et al, 2018), R&D project selection (Hassanzadeh et al, 2012;Collan and Luukka, 2014), patent portfolio management (Collan et al, 2013), valuation of large irreversible investments (Collan, 2011). Most of the previous applications have similarities to RE policy alternative analysis and comparison.…”
Section: Results and Visualizationmentioning
confidence: 99%